Parental education and wages: evidence from China - Yuanyuan Chen; Shuaizhang Feng (Institute for the Study of Labor (IZA), 2009)
Using nationally representative data in China, we find substantial positive partial correlations of both parents' education with one's wage. In addition, returns to father's education are higher in more monopsonistic and less meritocratic labor markets, including non-coastal regions, the state-owned sector, and the early periods of the reform era. The opposite is, however, true with respect to mother's education. Overall, the empirical evidence is consistent with the story that father's education mainly indicates family connections useful for locating a better-paying first job, while mother's education primarily captures unmeasured ability.
urn:nbn:de:101:1-20090619133
Keywords: J30; J62; 330; Parental education; wages; family connections; unmeasured ability; Lohn; Familiensoziologie; Soziales Netzwerk; Bildungsniveau; Eltern; China